Beyond the valley of the dolls - Meyer, Russ 1922-2004; Ebert, Roger 1942-2013; Phillips, Stu 1929- (The Criterion Collection, 2016)
"Eine Frauenpopgruppe wird berühmt und lernt das wilde Leben der Rauschgift- und Sexparties kennen. [...] Der im Stil eines Comics inszenierte Film gilt mittlerweile als Kultobjekt" [filmdienst.de]
Original: USA 1970
Two-dvd special edition features: audio commentary from 2003 featuring screenwriter Roger Ebert ; audio commentary from 2006 featuring actors Dolly Read, Cynthia Myers, Harrison Page, John LaZar, and Erica Gavin ; new interview with filmmaker John Waters ; episode from 1988 of the "Incredibly strange film show" on director Russ Meyers ; Q&A about the film from 1992 featuring Meyer, Ebert, LaZar, and Read; and actors David Gurian, Charles Napier, Michael Blodgett, and Edy Williams, with host Michael Dare ; interview with cast members from 2005 ; 'Above, beneath, & beyond the valley'; 'Look on up at the bottom'; 'The best of "Beyond"'; 'Sex drugs music & murder'; and 'Casey & Roxanne', five documentaries from 2006 about the making of the film, featuring the cast and crew ; screen tests ; trailers ; PLUS: a booklet featuring an essay by film critic Glenn Kenny and excerpts from a 1970 account in UCLA 'Daily Bruin' of a visit to the film's set
Bildformat 2.35:1 aspect ratio
Keywords: Beyond the valley of the dolls; Film; DVD-Video